LOAD-BEARING CAPACITY OF NON-MEMBRANE ROOFING SLABS AND FLOOR SLABS WITH EXTERNAL REINFORCEMENT USING STEEL PROFILED DECKING AND BAR REINFORCEMENT - Petriv, Vasyl (Theory and practice of design, 2025)
Purpose. The article considers the design of a multi-hollow ribbed reinforced concrete floor and roof slab with external reinforcement using steel profiled decking and bar reinforcement. The purpose is to increase the specific load-bearing capacity of the structure while reducing material consumption and labor costs for manufac- turing. Methodology. The proposed technical solution involves the use of a void former in the form of cardboard tubes placed in the stretched zone between the cor- rugations of the corrugated decking, which allows you to reduce the volume of con- crete without deteriorating strength characteristics. The profiled decking simultane- ously performs the functions of fixed formwork and longitudinal reinforcement, and due to its geometry it provides reliable adhesion to concrete and eliminates the need to install transverse reinforcement. The practical use of decking with a corrugation height of 75 mm has allowed to reduce the mass of the slabs by up to 50 % and re- duce the labor intensity of production by 25–40 % compared to traditional reinforced concrete structures. The paper presents the calculation prerequisites and dependencies for determining the strength of the slab, including determining the depth of the compressed zone, the stress in the corrugated sheet, the position of the neutral axis and the bending moment. Results. Bench tests confirmed the compliance of the adopted calculation model, which is based on the hypothesis of flat sections and the Prandtl diagram. The deviation between the calculated and actual moment of crack formation does not exceed 10 %, and the magnitude of deflections at the standard load decreased by an average of 20–25 %. It was established that increasing the height of the corrugation and the thickness of the steel significantly increases the rigidity of the structure and its crack resistance. The proposed parameters (corrugation height ≥60 mm, thickness ≥0.7 mm, diameter of the void formers 70–120 mm) provide the optimal ratio of strength, mass and manufacturability. The results obtained can be used to design effective composite floor slabs and roofing for civil and industrial construction. Scientific novelty. The design of a multi-hollow ribbed reinforced concrete floor and roof slab has been improved by using external reinforcement with profiled decking and bar reinforcement in combination with void formers, which made it possible to solve the problem of reducing the mass and increasing the rigidity of the structure in a new way while maintaining its strength. Practical relevance. The results obtained provide the possibility of designing effective composite floor slabs and roof coverings for civil and industrial construction with an optimal ratio of strength, mass and manufacturability, which contributes to reducing labor costs and material consumption in construction practice.